Discontinuous Digital Image Correlation to reconstruct displacement and strain fields with discontinuities: Dislocation approach. (15th February 2018) - Hassan, Ghulam Mubashar; Dyskin, Arcady V.; MacNish, Cara K.; Pasternak, Elena; Shufrin, Igor
Highlights: Introducing a technique to reconstruct displacement fields with discontinuities. Introduced technique can measure the discontinuities openings and angles. Examined the performance using simulated images. Examined the performance using images obtained in laboratory experiments. Found the technique to have accuracy close of 1/100th of a pixel for an image. Abstract: Reconstruction of strain and displacement fields from surface images of materials and structures in the presence of discontinuities is a challenging task. Digital Image Correlation (DIC) – a commonly used technique to reconstruct displacement and strain fields when deformation is continuous – fails in the presence of discontinuities, including cracks and crevices. This paper presents a novel and entirely automated technique, Discontinuous Digital Image Correlation (DDIC), to reconstruct displacement and strain fields with high accuracy from images when deformation is either continuous or discontinuous. The technique is based on introducing additional parameters that characterize the discontinuity: the direction of the tangent to the discontinuity line and the corresponding Burgers vectors which express the difference in displacements at the opposite sides of the discontinuity line. The proposed technique is validated using synthetic images as well as images obtained from laboratory experiments. The results show that DDIC is able to reconstruct the displacement fields around discontinuities with a subpixel accuracy close to 1 / 100 th of a pixel with a suitable surface pattern. It is also able to recover the size and angle of the discontinuity.